2016
DOI: 10.1016/j.rpto.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

How do servant leaders ignite absorptive capacity? The role of epistemic motivation and organizational support

Abstract: This study examines the role of servant leadership in absorptive capacity. Data from manufacturing and service sector organizations found that: a) there was moderation of servant leadership influence on knowledge identification through POS by high need for cognition, b) there was moderation of servant leadership influence on knowledge application through POS by low time pressure, and c) POS mediated relationship between servant leadership and knowledge dissemination. The findings illustrate and support the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 100 publications
1
5
0
1
Order By: Relevance
“…Slack includes both time and resources. In terms of time, for example, a study of 182 employees in the manufacturing and service sector found that low time pressure was positively associated with employees’ knowledge application, whereas high time pressure led to withholding knowledge application as they focused on task completion instead (Rai and Prakash, 2016). In terms of resources, a study of 190 business unit managers in Belgium found that budgetary slack was associated with innovation and the adoption of longer time horizons.…”
Section: New Ways Of Leadingmentioning
confidence: 99%
“…Slack includes both time and resources. In terms of time, for example, a study of 182 employees in the manufacturing and service sector found that low time pressure was positively associated with employees’ knowledge application, whereas high time pressure led to withholding knowledge application as they focused on task completion instead (Rai and Prakash, 2016). In terms of resources, a study of 190 business unit managers in Belgium found that budgetary slack was associated with innovation and the adoption of longer time horizons.…”
Section: New Ways Of Leadingmentioning
confidence: 99%
“…Another point of view that could be better understood in future studies refers to the analysis of different kinds of employees, as the literature suggests the actions of supervisor in constructing the levels of perceived organizational support are determinant (Rai & Prakash, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, several studies propose it as well that, moral emotions are agent-driven or recipient driven as explained by a study for studying moral emotions as implications for employee's behaviour (Pietersen, 2018;Rai & Banerjee, 2019;Rai & Prakash, 2016). Moral emotions help to elevate prosocial behaviour among employees.…”
Section: Discussionmentioning
confidence: 99%